2016
DOI: 10.18383/j.tom.2016.00229
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between 3-Scan Trace and Diagonal Body Diffusion-Weighted Imaging Acquisitions: A Phantom and Volunteer Study

Abstract: Diagonal diffusion-weighted imaging (dDWI) uses simultaneous maximized application of 3 orthogonal gradient systems as opposed to sequential acquisition in 3 directions in conventional 3-scan trace DWI (tDWI). Several theoretical advantages of dDWI vs. tDWI include reduced artifacts and increased sharpness. We compared apparent diffusion coefficient (ADC) quantification and image quality between monopolar dDWI and tDWI in a dedicated diffusion phantom (b = 0/500/900/2000 s/mm 2 ) and in the abdomen (b = 50/400… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Acceptable interplatform reproducibility in ADC values has been reported, including between 1.5 T and 3 T systems [3741]. Recently, we have reported excellent inter-platform reproducibility (1.5 T vs 3 T) of ADC using a dedicated DWI phantom (coefficient of variation CV < 7%), as well as in healthy volunteers (CV < 13.5%) [39].…”
Section: Methodsmentioning
confidence: 88%
“…Acceptable interplatform reproducibility in ADC values has been reported, including between 1.5 T and 3 T systems [3741]. Recently, we have reported excellent inter-platform reproducibility (1.5 T vs 3 T) of ADC using a dedicated DWI phantom (coefficient of variation CV < 7%), as well as in healthy volunteers (CV < 13.5%) [39].…”
Section: Methodsmentioning
confidence: 88%
“…In addition, complex averaging with phase correction is performed for opt-DWI in form of an adaptive combination, which can improve contrast-to-noise ratio and provide more exact ADC values by removing signal offsets. 29,30 A phantom and volunteer study at 3 T already demonstrated the superiority of diagonal DWI versus trace DWI regarding image quality, 31 and Corcuera-Solano et al 32 showed a comparable image quality while at the same time reducing the acquisition time in prostate MRI. The acquisition time is of special importance in daily clinical practice.…”
Section: Discussionmentioning
confidence: 98%
“…This scheme switches all 3 gradients simultaneously rather than sequentially with maximum amplitude; hence, it allows a lower echo time than does 3-scan trace and significantly reduces the scan time. Some studies reported that diagonal-DWI (d-DWI) demonstrated equivalent tumor detection, image quality, and ADC values as did the 3-scan trace DWI (t-DWI) with substantially reduced acquisition time (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…This reduction of d-DWI acquisition time can be achieved at a cost of lower SNR compared to t-DWI. Theoretically, to preserve SNR, the averages of d-DWI should be increased by a factor of 3 compared to t-DWI because the loss in SNR has a factor of √3 due to the single diffusion acquisition compared with the sequential acquisition of 3 diffusion directions in t-DWI (20). Although higher averages were set for iShim DWI compared to SS-EPI DWI to compensate for the loss in SNR, Siemens engineers chose a lower number of averages by factors of 2-2.5 to shorten the total scan time.…”
Section: Discussionmentioning
confidence: 99%